Evidence of Seasonal Uplift in the Argentière Glacier (Mont Blanc Area, France). Issue 7 (21st July 2022) - Vincent, Christian; Gilbert, Adrien; Walpersdorf, Andrea; Gimbert, Florent; Gagliardini, Olivier; Jourdain, Bruno; Roldan Blasco, Juan Pedro; Laarman, Olivier; Piard, Luc; Six, Delphine; Moreau, Luc; Cusicanqui, Diego; et al.
Abstract: The hydromechanical processes by which basal water controls sliding at the glacier bed are poorly known, despite glacier basal motion being responsible for a large part of ice flux in temperate alpine glaciers. Previous studies suggest that sliding strongly relates to the quantity of water being stored at the ice‐bedrock interface. However, this water storage is difficult to quantify accurately on the basis of surface‐motion observations, given that uplift can also be affected by changes in vertical‐strain rates and sliding velocity change. Here, we use a comprehensive data set of in situ measurements performed over 2 years on the Argentière Glacier in the French Alps to investigate the relationships between horizontal and vertical velocities, basal sliding, subglacial runoff and bed separation. We observe strikingly large uplifts varying spatially between 0.20 and 0.90 m over the winter/spring seasons between January and June and with a consistent spatial pattern from 1 year to another. We show, based on observations and three dimensional ice‐flow modeling, that these large uplifts cannot be explained solely by changes in strain rates or in sliding up an inclined bed. Our results reveal that more than 80% of the observed uplift is related to enhanced bed separation through cavitation, allowing us to estimate the volume occupied by water‐filled subglacial cavities. Our interpretation of uplift being mainly caused by increased cavitation is also consistent with an associated increase in the observed surface horizontal velocity. These findings provide important observational constraints for testing subglacial hydrological models. Plain Language Summary: Glacier basal motion is responsible for a large part of ice flux in temperate alpine glaciers and outlet glaciers of ice sheets. However, the hydromechanical processes by which basal water controls sliding at the glacier bed are poorly known in large part because observations are very scarce. Consequently, the impact of surface melting and meltwater input on the future of mountain glaciers and outlet glaciers of ice sheets remains unclear. Here, we use a comprehensive data set of in situ measurements performed over 2 years on the Argentière Glacier in the French Alps, complemented by state‐of‐the‐art ice flow and hydrology modeling, to investigate changes in water storage at the ice‐bedrock interface. We find strikingly large uplifts ranging between 0.20 and 0.90 m over the winter/spring seasons in the ablation zone. We show that this uplift is mostly related to enhanced bed separation as a result of increased basal water storage. We expect this study to be helpful to the glaciological community studying basal sliding and its modulation by sub‐glacial hydrology with a view of improving predictions of the future behavior of mountain glaciers and outlet glaciers of ice sheets. Key Points: We investigate horizontal, vertical velocities, basal sliding and subglacial runoff on the Argentière glaciers (French Alps) We find large uplifts ranging between 20 and 90 cm over the winter/spring seasons over a large part of ablation zone We show that the observed uplift is very likely related to enhanced bed separation as a result of increased storage of basal water